Neuroimaging of situational urgency and incontinence provoked by personal urgency cues. Issue 1 (27th September 2021) - Clarkson, Becky D.; Wei, Zhiyang; Karim, Helmet T.; Tyagi, Shachi; Resnick, Neil M.; Salkeld, Ronald P.; Conklin, Cynthia A.
Abstract: Introduction: Situational triggers for urinary urgency and incontinence (UUI) such as "latchkey incontinence" and running water are often reported clinically, but no current clinical tools exist to directly address symptoms of UUI provoked by environmental stimuli. Previously we have shown that urgency and leakage can be reproduced during urodynamic studies with exposure to personal urgency‐related images. Here we investigate the neural signatures associated with such situational triggers to inform potential therapies for reducing reactivity to these personal urgency‐related cues among women with situational UUI. Method: We recruited 23 women with situational UUI who took photographs of their personal "urgency trigger" and "safe" situations and were exposed to them in a magnetic resonance imaging (MRI) scanner. We identified brain areas that were more active during urgency versus safe image exposure. Results: We found that, during urgency image exposure, main components of the attention network and decision‐related processes, the middle and medial frontal gyri, were more active ( p < 0.01). In addition, areas well known to be involved in the continence mechanism, such as the cingulate and parahippocampal areas, were also more active during urgency image exposure. Conclusion: Exposure to personal situational urgency images activated different areas of the brain compared with safe environments, highlighting the complex brain mechanisms that provoke real‐world urgency. Using brain and behavioral‐based therapies which target the attentional areas identified here and extinguish cue reactivity might reduce symptom burden in this subset of UUI sufferers.